Is the Relationship Between Stratospheric Arctic Vortex and Arctic Oscillation Steady?. Issue 19 (29th September 2021) - Hu, Dingzhu; Guan, Zhaoyong; Liu, Meichen; Wang, Tao
Abstract: The connections between the stratosphere and troposphere, for example, the stratospheric Arctic vortex (SAV) and Arctic Oscillation (AO), have been paid attention by scientists and the public in recent years. Previous studies suggested that the coupling between the stratosphere and troposphere is the strongest in winter. However, whether the link between SAV and AO during boreal winter on interannual timescales is steady is still unknown. Our results show that the interannual relationship between the SAV in early winter and AO in late winter during 1958–2018 is unsteady and has experienced a remarkable interdecadal change around the 2000s, with large and statistically significant positive correlations before the 2000s but small and insignificant correlations after the 2000s. The weakened linkage between the SAV and AO after the 2000s is possibly caused by (a) the weakened downward effect of SAV on the North Atlantic and polar sectors of AO, and (b) the opposite signs of sea level pressure (SLP) in the North Pacific and North Atlantic. The links of SAV‐AO are enforced (weakened) when AO‐related SLP anomalies over the North Pacific are the same (opposite) signs of those over the North Atlantic before (after) the 2000s. Differences in the tropospheric state over the North Pacific during two periods might be jointly contributed by the SAV and the SAV‐related significant (insignificant) sea surface temperature anomalies over central North Pacific in the earlier (latter) period. Our results may provide evidences to improve the predictability in seasonal or interannual timescales forecasts of weather and climate at mid‐latitudes. Key Points: The link of stratospheric Arctic vortex (SAV)‐Arctic Oscillation (AO) has experienced a remarkable interdecadal change around the 2000s The opposite signs of the SAV‐related sea level pressure anomalies over the North Pacific and North Atlantic after the 2000s weaken the links of SAV‐AO Differences in AO's Pacific sector around the 2000s are jointly contributed by the SAV and its related sea surface temperature anomalies over central North Pacific